Phenotype frequencies of autosomal minor histocompatibility antigens display significant differences among populations - Spierings, Eric; Hendriks, Matthijs; Absi, Léna; Canossi, Angelica; Chhaya, Sonal; Crowley, John; Dolstra, Harry; Eliaou, Jean-François; Ellis, Tom; Enczmann, Jürgen; Fasano, Maria E.; Gervais, Thibaut; et al. (PLoS Genetics, 2007)
Minor histocompatibility (H) antigens are allogeneic target molecules having significant roles in alloimmune responses after human leukocyte antigen-matched solid organ and stem cell transplantation (SCT). Minor H antigens are instrumental in the processes of transplant rejection, graft-versus-host disease, and in the curative graft-versus-tumor effect of SCT. The latter characteristic enabled the current application of selected minor H antigens in clinical immunotherapeutic SCT protocols. No information exists on the global phenotypic distribution of the currently identified minor H antigens. Therefore, an estimation of their overall impact in human leukocyte antigen-matched solid organ and SCT in the major ethnic populations is still lacking. For the first time, a worldwide phenotype frequency analysis of ten autosomal minor H antigens was executed by 31 laboratories and comprised 2,685 randomly selected individuals from six major ethnic populations. Significant differences in minor H antigen frequencies were observed between the ethnic populations, some of which appeared to be geographically correlated.
Gesehen am 02.06.2021